2022
DOI: 10.1016/j.ocecoaman.2021.105995
|View full text |Cite
|
Sign up to set email alerts
|

Legal issues and challenges in addressing the coronavirus outbreak on large cruise ships: A critical examination of port state measures

Abstract: International cruises have drawn worldwide attention since the outbreak of coronavirus (COVID-19). This article first examines the legal issues, challenges and impact of the pandemic on large cruise ships, like the Diamond Princess, and then probes into corresponding pandemic preventive measures which port states employ. A State is obliged under the International Health Regulations 2005 (IHR) to grant foreign cruise ships free pratique , but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…37 Research conducted during the pandemic showed that "29% of working women with young children found it difficult to concentrate on their work due to family responsibilities as compared to 16% of working men in the same situation". 38 During the epidemic, women are more likely to cut back on their work hours or stop working altogether to take care of their children, 39 reinforcing traditional gender roles and exacerbating previous imbalances.…”
Section: Findings On the Impact Of The Pandemic On Women's Working Li...mentioning
confidence: 99%
See 1 more Smart Citation
“…37 Research conducted during the pandemic showed that "29% of working women with young children found it difficult to concentrate on their work due to family responsibilities as compared to 16% of working men in the same situation". 38 During the epidemic, women are more likely to cut back on their work hours or stop working altogether to take care of their children, 39 reinforcing traditional gender roles and exacerbating previous imbalances.…”
Section: Findings On the Impact Of The Pandemic On Women's Working Li...mentioning
confidence: 99%
“…38 Eurofound (2020), Women and the labour market: has COVID rolled back recent gains, available at https://www.eurofound.europa.eu/publications/policy -brief/2020/women-and-labour-market-equality-has-covid-19-rolled-back-recen t-gains. 39 Alon T., Doepke, M., Olmstead-Rumsey, J., Tertilt, M. ( 2020), 'This Time It's Different: The Role of Women's Employment in a Pandemic Recession', IZA Institute of Labour Economics, Discussion Paper Series No 13562, p. 4, available at https://covid-19.iza.org/publications/dp13562/. 40 European Institute for Gender Equality (2020), Gender Equality Index 2020: Digitalisation and the future of work, available at https://eige.europa.eu/public ations/gender-equality-index-2020-digitalisation-and-future-work.…”
Section: Findings On the Impact Of The Pandemic On Women's Working Li...mentioning
confidence: 99%
“… Ito et al (2020) investigated the relationship between cruise ship size and the number of COVID-19 confirmations. Sun and Zhao (2022) examined disease preventive measures and isolation measures on board against COVID-19 by the port States. Pan et al (2021) investigated the attitudes of 759 consumers towards the cruise industry during the COVID-19 pandemic, and the results showed that cruise companies should increase investment in epidemic prevention and advertising to restore consumer trust and achieve market recovery.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In response to the design flaws revealed by the Diamond Princess, such as the space layout and air conditioning system, the cruise line invested much money to improve the safety and epidemic prevention of the cruise ship ( Sun and Zhao, 2022 ), including (1) Each stateroom, crew room, and public areas are equipped with 100% fresh air circulation system. (2) Medical center with isolation wards.…”
Section: Introductionmentioning
confidence: 99%
“…From these three stages, we can determine that effective management of international public health can be accomplished if the governance objectives are clearly defined, there exists active cooperation among stakeholders, the existing legal basis is sufficient and concrete, and the governance tools are specific and practical.The COVID-19 pandemic has created an unprecedented health and social scenario ( Kane et al, 2021 ; Alfonso et al, 2021 ; Armenio et al, 2021 ; Fernández-González et al, 2022 ) and altered humans' everyday lives in all aspects, and of course, the tourism cruise industry is no exception. Since the COVID-19 outbreak, confirmed cases on international cruise ships, such as “Diamond Princess”, “Costa Serena”, “Westerdam” and “Grand Princess”, have focused the international community's attention on the dangers of cruise confinement ( Sun and Zhao, 2022 ). Despite past norovirus outbreaks on cruise ships and despite the severity of the situation derived from COVID-19, countries have not reached a consensus on the prevention, control, and management of this kind of public health situation in particular environments, such as cruise ships.…”
Section: Introductionmentioning
confidence: 99%